Meningkatkan Keterampilan Penulisan Teks Cerita Inspiratif dengan Menggunakan Media Comik Strip pada Siswa Kelas IX di SMP Negeri 1 Alasa Talumuzoi - Ziliwu, Bonafetura Niamonio; Yu'min Hakim Gea, Wecan Kartika Hidayati Gea; Gea, Yu’min Hakim; Gea, Wecan Kartika Hidayati; Zendrato, Krisna Ifariani; Zebua, Vemky The Better (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The aim of this research is to improve students' ability to write inspirational stories using comic strip media. This Classroom Action Research was carried out in two cycles, with data collection, observation, tests and documentation. The research object was 30 students in class IXA of SMP N 1 Alasa Talumuzoi, consisting of 14 men and 16 women. The results of the research show that the use of comic strip media can improve students' inspirational story text writing skills in cycle 1 with an average of 56.7% and cycle 2 with an average of 96.67%. The researcher concluded that: the use of comic strip media in planning and implementing learning carried out by researchers in teaching material on writing inspirational story texts can improve the skills of writing inspirational story texts in class IX A students of SMP Negeri 1 Alasa Talumuzoi